2002
DOI: 10.1046/j.1365-2036.2002.01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical decision analysis of endoscopic surveillance of Barrett’s oesophagus to prevent oesophageal adenocarcinoma

Abstract: INTRODUCTIONIn a subgroup of patients with gastro-oesophageal re¯ux disease, the normal squamous epithelium of the distal oesophagus is replaced by columnar lined epithelium with intestinal metaplasia. The condition of intestinal metaplasia in the distal oesophagus is known as Barrett's oesophagus. Barrett's oesophagus carries a more than 30-fold increased risk of developing oesophageal adenocarcinoma. 1 Estimates for the annual incidence rate of adenocarcinoma range between 0.2% and 2% in patients with Barret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 37 publications
(43 reference statements)
0
45
0
2
Order By: Relevance
“…Of the 177 remaining images, 49 corresponded to a diagnosis of IMC/HGD, 15 to LGD, 8 to IGD, 100 to SIM, and 5 to gastric mucosa. Of the 65 discarded images, 20 corresponded to a diagnosis of IMC/HGD, 13 LGD, 2 IGD, 29 SIM, and 1 gastric mucosa. The agreement between pathologists' diagnoses of IMC/HGD was excellent (κ = 0.89).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 177 remaining images, 49 corresponded to a diagnosis of IMC/HGD, 15 to LGD, 8 to IGD, 100 to SIM, and 5 to gastric mucosa. Of the 65 discarded images, 20 corresponded to a diagnosis of IMC/HGD, 13 LGD, 2 IGD, 29 SIM, and 1 gastric mucosa. The agreement between pathologists' diagnoses of IMC/HGD was excellent (κ = 0.89).…”
Section: Resultsmentioning
confidence: 99%
“…Some computer-modeling studies have concluded that screening and surveillance can be cost-effective under certain circumstances, but such studies are not definitive. 43,44 Despite the lack of high-quality evidence to support the practice, medical societies currently recommend endoscopic screening for Barrett's esophagus in patients with chronic GERD symptoms who have at least one additional risk factor for esophageal adenocarcinoma, such as an age of 50 years or older, male sex, white race, hiatal hernia, elevated body-mass index, intraabdominal body-fat distribution, or tobacco use. 2,12,13,45 If the screening examination does not reveal Barrett's esophagus, no further endoscopic screening for the condition is recommended.…”
Section: Epidemiol Ogymentioning
confidence: 99%
“…A number of computer models have supported the practice of endoscopic screening and surveillance for Barrett's esophagus [34][35][36][37][38][39][40][41]. Table 1 summarizes the results of five Markov models that examined the issue of screening middle-aged patients with GERD symptoms for Barrett's esophagus.…”
Section: Computer Modelsmentioning
confidence: 99%